Anaerobic Co-Digestion of Food Waste with Sewage Sludge: Simulation and Optimization for Maximum Biogas Production - Wai Lin Cheong; Yi Jing Chan; Timm Joyce Tiong; Woon Chan Chong; Worapon Kiatkittipong; Kunlanan Kiatkittipong; Mardawani Mohamad; Hanita Daud; I. Wayan Koko Suryawan; Mega Mutiara Sari; Jun Wei Lim (My University, 2022)
Anaerobic co-digestion (ACD), where two or more substrates are digested simultaneously, is able to prevent the problems associated with mono-digestion. The aim of this study is to develop a simulation model of ACD of food waste (FW) with sewage sludge (SS) for biogas production coupled with pre-treatment, sludge handling and biogas upgrading using SuperPro Designer v9.0. The Design Expert v13 is employed to perform optimization and evaluate the effect of hydraulic retention time (HRT), sludge recycle ratio, water to feed ratio (kg/kg) and SS to FW ratio (kg/kg) on the methane flow, chemical oxygen demand (COD) and volatile solids (VS). The results show that the methane yield of 0.29 L CH4/g COD removed, COD removal efficiency of 81.5% and VS removal efficiency of 69.2% are obtained with a HRT of 38.8 days, water to feed ratio (kg/kg) of 0.048, sludge recycle ratio of 0.438 and SS to FW ratio (kg/kg) of 0.044. Economic analysis has shown this study is feasible with a payback time of 6.2 years, net present value (NPV) of $5,283,000 and internal return rate (IRR) of 10.2%. This indicates that the ACD of FW and SS is economically feasible in a larger scale.
Keywords: Biogas; Food Waste; Hydraulic retention time; Sewage sludge; Biogas Production; Anaerobic Digestion and Biogas Production